IMPLEMENTASI PROGRAM JAMINAN SOSIAL TENAGA KERJA (JAMSOSTEK) di PT BIOTIS NUSANTARA CABANG KOTA MEDAN - JOSUA F PASARIBU (Welfare StatE, 2013)
The present national development has enlargednworking oppurtunity which in the same time produces income for the workers and their family. Those income, however, can be lessened or even vanished due to several risks such as accident, dissability, illness, elderly and death. This research is aimed at finding out the implementation of worker social security program at PT Biotis Nusantara , branch Medan. The type of the research is descriptive statistical analysis taking 25 employees of PT Biotis Nusantara as its population. Data gathering is done through questionaire, interview and observation. According to the research, it is found out that the implementaion of worker social security program at PT Biotis Nusantara is not fully subjected to the established rules. This is due to the lack of PT Biotis Nusantara supervision towards its registered member and the roles that PT Biotis Nusantara has not maximally played. Keywords: Worker, Implementation, Social Security Program